2017
DOI: 10.1159/000455861
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Peripheral Blood Lymphocytes between Brand-Name and Generic Tacrolimus Used in Stable Liver Transplant Recipients

Abstract: Objectives: In this study, peripheral blood lymphocytes were compared between a brand-name and a generic tacrolimus group in stable liver transplant recipients. Subjects and Methods: Sixteen patients who underwent ABO-compatible living donor liver transplants between 2012 and 2013 and had stable graft function were included in this study. Ten patients received brand-name tacrolimus and 6 patients received generic tacrolimus. CD3, CD4, CD8, γδ, CD4+FoxP3+, and CD3-CD56+ T cells were analyzed in peripheral blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(37 reference statements)
1
0
0
Order By: Relevance
“…Only the level of CD4+Foxp3+ T cells was higher in the brand-name tacrolimus group than in the generic tacrolimus group after LT. 13 The present study again demonstrated that the efficacy and safety of generic tacrolimus were not different from those of brand-name tacrolimus. Tacrolimus has a narrow therapeutic index and is subject to routine therapeutic drug monitoring and dose adjustment.…”
Section: Discussionsupporting
confidence: 64%
“…Only the level of CD4+Foxp3+ T cells was higher in the brand-name tacrolimus group than in the generic tacrolimus group after LT. 13 The present study again demonstrated that the efficacy and safety of generic tacrolimus were not different from those of brand-name tacrolimus. Tacrolimus has a narrow therapeutic index and is subject to routine therapeutic drug monitoring and dose adjustment.…”
Section: Discussionsupporting
confidence: 64%